Diagnóstico socioeconómico de los propietarios de viveros del sector Banco de Arena, cantón Milagro, Ecuador - Tixi Lemache, Antonny Brayan (2022)
The present research entitled Socioeconomic diagnosis of the owners of nurseries located in the Banco de Arena sector, km 4 via Milagro – Naranjito is of great importance because it has obtained appreciable information on the current situation inwhich these small entrepreneurs live, whose businesses are adjacent to the road andoffer a great variety of natural flowers, among them: roses, sunflowers, jasmine, palms, ferns, grass, among the most relevant and cacti, within these are countless species in trend. The study aims to analyze the social and economic situation of nursery owners in the Banco de Arena sector. The methodology used was of mixedapproach, with emphasis on the quantitative when using the statistical method; qualitatively, interpretation was fundamental to the analysis; the scope of the studywas descriptive in detailing the situation and conditions of producers and nurseries, and also had a marked documentary character due to the meticulous search forinformation………